Analysis of the Stiffness Characteristic of Three Types of Four-bar Flexure Hinge Mechanism based on ANSYS - Wang Chengtao; Wang Yuqiao; Yang Xuefeng; Liu Yufei; Wei Huaxian; Sheng Lianchao (Jixie chuandong)
The single parallel four-bar flexure hinge mechanism is widely used as the prismatic pair of the ultra-precision stage and precision sensors. Since the ultra-precision stage produces the displacement depended on it,so the stiffness of single parallel four-bar flexure hinge mechanism has a great influence on the positioning accuracy of ultra-precision stage. Aiming at three types of single parallel four-bar flexure hinge mechanisms,the theoretical calculation of stiffness is carried out,then,the mechanisms are analyzed by the finite element software ANSYS 12. 0. The influences of different external dimensions on the stiffness and relationship between stiffness of three types of mechanisms are obtained through comparison and analysis,a reference for their application occasions and the selection in MEMS design is provided.